Substantiation of the parameters of the technological process of production of facade slabs with imitation of natural stone (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article considers the technology of obtaining facade slabs with imitation of natural stone. The results of experimental industrial work on the production of prototypes of facade slabs with imitation of natural stone in the conditions of the production workshop of the State of emergency Gapirov are presented. Based on the results of the tests, technological recommendations have been developed to rationalize the parameters of the manufacture of facade slabs with the addition of man-made waste in the form of marble chips and granite screenings.
Keywords: facade slabs, decorative concrete, screening, pigment, imitation of natural stone, vibration treatment